Automated Immunohistochemistry as an Alternative to Conventional Immunohistochemistry for Analyzing the Expression of BCL2 and Ki-67 in Diffuse Large B-Cell Lymphoma Patients - Yimpak, Phuttirak; Bumroongkit, Kanokkan; Tantiworawit, Adisak; Rattanathammethee, Thanawat; Aungsuchawan, Sirinda; Daroontum, Teerada (Biomedical Sciences and Clinical Medicine, 2025)
Objective Diffuse large B-cell lymphoma (DLBCL) is the most common subtype of non-Hodgkin lymphoma. Immunohistochemistry (IHC) is widely used to assess prognostic markers such as BCL2 and Ki-67. Conventional IHC relies on manual staining and visual estimation by pathologists, while automated IHC incorporates computer-based image analysis. This study aimed to evaluate the level of agreement between these two IHC workflows in assessing BCL2 and Ki-67 expression in DLBCL patients. Methods Formalin-fixed, paraffin-embedded tissue samples from nodal and extranodal sites of 42 and 60 DLBCL cases were analyzed for BCL2 and Ki-67, respectively. Conventional IHC involved manual staining and evaluation by a pathologist in 10.00% increments. Automated IHC used the Ventana BenchMark ULTRA system with digital image analysis. Expression levels of the two systems were compared using paired t-tests, intraclass correlation coefficients (ICC), Pearson’s correlation, and Bland–Altman plots. Results For BCL2, no significant difference was found between the two methods (mean difference = 5.79%, p = 0.103), with moderate to good agreement (ICC = 0.739) and strong correlation (r = 0.772). For Ki-67, patho-logist-based assessment yielded significantly higher values (mean difference = 13.91%, p < 0.001), with moderate agreement (ICC = 0.569) and strong correlation (r = 0.688). Bland–Altman analysis confirmed acceptable limits of agreement, although a slight underestimation in the automated Ki-67 results was observed. Conclusions Automated IHC showed moderate to good agreement with conventional IHC, particularly for BCL2. Despite some differences in Ki-67 quantification, both methods demonstrated consistent trends. Auto-mated IHC offers reproducibility and scalability, making it a promising complementary tool in pathology.